(untitled) (Global Journal of Human-Social Science, 2024)
This article presents the observations of mile Jaques-Dalcroze based on his pedagogical practice on the relationship between voice and body movement in the musical experience for the construction of attentive and creative listening not only capable of analyzing and reproducing music as an instrument of execution but remaining sensitive between repetitions weaving relationships with other experiences through rhythm bringing together different references expanding repertoires and deepening musical reception to interpret music in a meaningful way in the interpersonal space in which it takes place whether for the musical performer or for the listener